The Global Diversity of Hemichordata - Tassia, Michael G.; Cannon, Johanna T.; Konikoff, Charlotte E.; Shenkar, Noa; Halanych, Kenneth M.; Swalla, Billie J. (PLOS ONE, 2016)
Phylum Hemichordata, composed of worm-like Enteropneusta and colonial Pterobranchia, has been reported to only contain about 100 species. However, recent studies of hemichordate phylogeny and taxonomy suggest the species number has been largely underestimated. One issue is that species must be described by experts, and historically few taxonomists have studied this group of marine invertebrates. Despite this previous lack of coverage, interest in hemichordates has piqued in the past couple of decades, as they are critical to understanding the evolution of chordates–as acorn worms likely resemble the deuterostome ancestor more closely than any other extant animal. This review provides an overview of our current knowledge of hemichordates, focusing specifically on their global biodiversity, geographic distribution, and taxonomy. Using information available in the World Register of Marine Species and published literature, we assembled a list of 130 described, extant species. The majority (83%) of these species are enteropneusts, and more taxonomic descriptions are forthcoming. Ptychoderidae contained the greatest number of species (41 species), closely followed by Harrimaniidae (40 species), of the recognized hemichordate families. Hemichordates are found throughout the world’s oceans, with the highest reported numbers by regions with marine labs and diligent taxonomic efforts (e.g. North Pacific and North Atlantic). Pterobranchs are abundant in Antarctica, but have also been found at lower latitudes. We consider this a baseline report and expect new species of Hemichordata will continue to be discovered and described as new marine habitats are characterized and explored.